IMPLEMENTASI NILAI NILAI PANCASILA DALAM BEST PRACTICE CORPORATE GOVERNANCE PERBANKAN INDONESIA - Heri Prasetyo; Heru Priyanto; Surifah Surifah (BBM (Buletin Bisnis & Manajemen), 2018)
The purpose of this research is to develop a model in implementing Pancasila values in the best practice corporate governance (IPCG) and to examine the relation between IPCG and banking performance in Indonesia. IPCG was measured by using index based on the CG principles which had been adjusted to the values of Pancasila. Bank performance was measured by using ROA, ROE, LDR, and OER.                The result shows that Pancasila values have been well implemented in the Indonesian banking. IPCG does not affect ROA and ROE, but negatively effects on LDR and OER, in which LDR becomes lower as IPCG becomes higher, meaning that it has less risk.